ANALISIS PENGARUH INDEKS PEMBANGUNAN MANUSIA, PDRB PER KAPITA DAN JUMLAH PENDUDUK TERHADAP JUMLAH PENDUDUK MISKIN DI KALIMANTAN SELATAN TAHUN 2010-2017 - FARADINA ANGGRAINI; RUSDIANSYAH RUSDIANSYAH (PPJP Universitas Lambung Mangkurat, 2019)
Poverty is one of an obstacle that faced by nearly all of countries around the world, mainly for the developing countries. Poverty may caused of many things such as the low level of education, low level of health, limitation of access towards goods and services, high level of unemployment, a high and rapid growth of population, low level of income, and others. This study aims to analyze the impact of Human Development Index, Gross Domestic Regional Product per capita and Population towards Population of Poor People in South Kalimantan. The method of analysis that using in this research is Ordinary Least Square (OLS) and by using panel data (pooled data) that is the combination of time series data started from 2010 until 2017 and cross section data of 13 regencies/cities in South Kalimantan. The analysis in this research doing by help of an Eviews 9 software.The result of this research shows that Human Development Index and Population have a positive effect and not significant towards poor population in South Kalimantan. Meanwhile Gross Domestic Regional Product has a negative effect and significant towards poor population in South Kalimantan. Those three variables have a significant effect simultaneously towards poor populations in South Kalimantan.Key words ; poor population, poverty, population, Human Development Index, GDRP Per capita